Role of Bala (Immunity) in Covid-19 Pandemic: An Ayurvedic Review - Gurav Vishal Prabhakar,; Gannur Prasadshakti G , (International Journal of Ayurveda and Pharma Research, 2021)
The whole world is suffering from the disaster COVID-19 pandemic caused by the novel Coronavirus SARS-CoV-2. This novel Coronavirus is extremely contagious and in short span of time it has evolved as a serious hazard to humanity. COVID-19 usually affects people with low immunity responses. No Confirmed treatment is available yet to overcome against COVID-19. Strengthening the immunity of human body is the best option to restrict COVID-19 infection by. This Study is a small effort to enlighten the Ayurvedic broad Concept of Bala which has a direct relation with Ojus & Vyadhikshamatva. This Ayurvedic Concept has the potential to built strong immunity against COVID-19 which may be helpful in this battle against the current scenario of the Disastrous COVID‑19 pandemic for the survival of human beings.